Process Optimization of Pontianak Aloe vera Powder (Aloe chinensis Beakker) as Raw Material for Hand body lotion - Supriyatna, Nana (Balai Riset dan Standardisasi Industri Pontianak, 2010)
Process optimization of Pontianak aloe vera powder (Aloe chinensis Beaker)Â as raw material for hand body lotion have been conducted on laboratory scale with the aim of obtaining the optimum conditions of processing technologies through the addition of maltodextrin and Carboxy Methyl Cellulase. The optimum results achieved at the ratio of maltodextrin to the CMC by 90%: 10%. Characteristics of aloe vera powder produced showing yellowish white color, water content of 8:56%, 5:50 pH, total solid Aloe 25.5%, weight flour ratio and fresh aloe vera leaves 1.5: 100, aloin content of 164.40 ppm, 257.08 ppm malic acid content, 10.32 ppm vitamin E and 1.4 x 105 colonies/g total bacteria. Making hand body lotion of aloe vera powder optimization results show the characteristic white color with a fragrant aroma, acidity (pH) 7:07, 10.34 ppm of malic acid, 1.1 x 104 colony/g total bacteria, and quite stable while storage.